The Diagrammatic Soergel Category and sl(N)-Foams, for N≥4 - Marco Mackaay; Pedro Vaz (International Journal of Mathematics and Mathematical Sciences)
For each N≥4, we define a monoidal functor from Elias and Khovanov's diagrammatic version of Soergel's category of bimodules to the category of sl(N) foams defined by Mackaay, Stošić, and Vaz. We show that through these functors Soergel's category can be obtained from the sl(N) foams.